2004
DOI: 10.1007/s00268-004-7364-x
|View full text |Cite
|
Sign up to set email alerts
|

Biliopancreatic Diversion in the Surgical Treatment of Morbid Obesity

Abstract: Biliopancreatic diversion is a malabsorptive technique of bariatric surgery that has gained wide acceptance in the Western world. It is performed in one of two ways: In its classic form it consists of partial gastrectomy with a Roux-en-Y gastroenterostomy; in its duodenal switch form a vertical sleeve gastrectomy is combined with a duodenoenterostomy. Both techniques realize diversion of biliopancreatic juice, thereby creating a mild form of malabsorption. Weight loss has been approximately 70% of initial exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 146 publications
(181 reference statements)
2
20
0
1
Order By: Relevance
“…As for weight loss, in our experience, as in Scopinaro et al's [3,[9][10][11][12] and in other [27][28][29][30][31][32] series, we observed that BPD allowed to obtain and to maintain a significant long-term weight loss.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…As for weight loss, in our experience, as in Scopinaro et al's [3,[9][10][11][12] and in other [27][28][29][30][31][32] series, we observed that BPD allowed to obtain and to maintain a significant long-term weight loss.…”
Section: Discussionsupporting
confidence: 68%
“…It is currently believed that BPD, as described by Scopinaro et al [9], and its subsequent successful modifications are effective in curing these diseases through malabsorption [7][8][9][10][11][12][27][28][29][30][31][32]. By contrast, the restrictive procedures, even when performed on a large scale, did not show the same efficacy, especially in controlling type 2 diabetes [27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This operation improves quality of life in the majority of patients 43 and carries a 30-day mortality of 0.3%. 44,45 It is recognized as a leading metabolic procedure in view of its low morbidity compared with other bypass procedures such as biliopancreatic diversion 46,47 and its metabolic superiority compared with non-bypass procedures such as gastric banding. 48 RYGB achieves a number of physiological effects as a consequence of bile flow alteration, reduction of gastric size, altered flow of nutrients, vagal manipulation, and gut hormone modulation.…”
Section: Etiology Of Hyperinsulinemic Hypoglycemiamentioning
confidence: 99%